Discover a world of knowledge at Westonci.ca, where experts and enthusiasts come together to answer your questions. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform.

Use f(x) = 3 - 2x2 - 2x and g(x) = 8x - 5 to determine what (f+g)(x) then write it in standard form

Sagot :

(f+g)x= f(x) + g(x)

= (3 - 2x² - 2x) + (8x - 5)

Then we will evaluate

We need to re-arrange first

= -2x² - 2x + 8x + 3 -5

= -2x² + 6x - 2

Hence;

(f+g)(x)= -2x² + 6x - 2